Toksisitas Campuran Ekstrak Daun Sirsak (Annona muricata) Dan Daun Kelor (Moringa oleifera) Terhadap Larva Nyamuk Aedes aegypti L. Dan Pemanfaatannya Sebagai Poster - Faysya Zuma Aljavi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Mosquitoes were known as vectors causing Dengue Hemorrhagic Fever (DHF), especially Aedes aegypti, which played a role in the transmission of the dengue virus. Vector control was conducted using natural biolarvicides, which were safer and more environmentally friendly than chemical larvicides. This study aimed to determine the Lethal Concentration 50% (LC₅₀) value of a mixture of soursop (Annona muricata) and moringa (Moringa oleifera) leaf extracts against Aedes aegypti larvae and its use as a poster. This study was an experimental study using a completely randomized design. The sample consisted of 300 early instar III–IV Aedes aegypti larvae. Treatments were applied at extract mixture concentrations of 100 ppm, 250 ppm, 500 ppm, 750 ppm, and 1000 ppm, with 100 ppm abate as a positive control and distilled water as a negative control. Each treatment was repeated three times with a 24-hour exposure period. Larval mortality data were analyzed using probit analysis with SPSS to determine the LC₅₀ value. The results showed that the LC₅₀ value of the extract mixture at 24 hours was 683.903 ppm, with a lower limit of 596.892 ppm and an upper limit of 751.075 ppm, indicating that the extract mixture was toxic to Aedes aegypti larvae. The results of the study were compiled into a poster and were validated by material experts, media experts, students, and the general public, with the validation results indicating that the poster was suitable as an information and learning medium.
FINALISASI oleh Arif 2026 Mei 26
Keywords: Aedes aegypti L.; Biolarvicides; LC₅₀; Mortality